Saturation monitoring of VX15/2503, a novel semaphorin 4D‐specific antibody, in clinical trials. Issue 2 (24th December 2015) - Fisher, Terrence L.; Seils, Jennifer; Reilly, Christine; Litwin, Virginia; Green, Lisa; Salkowitz‐Bokal, Janelle; Walsh, Robin; Harville, Sarah; Leonard, John E.; Smith, Ernest; Zauderer, Maurice
Abstract : Background: Receptor occupancy, or saturation, assays are often utilized in preclinical and clinical development programs to evaluate the binding of a biologic to a cellular target. These assays provide critical information regarding the dose of drug required to "saturate" the target as well as important pharmacodymamic (PD) data. A flow cytometric method was developed to measure the degree of Semaphorin 4D (SEMA4D; CD100) saturation by VX15/2303, an investigational monoclonal antibody specific for SEMA4D. Methods: The assay detects VX15/2503, a human IgG4 specific for SEMA4D, with an IgG4 ‐specific monoclonal antibody. Results: Data generated allowed assessment of two related SEMA4D‐specific pharmacodynamic (PD) markers: (1) The measurement of cellular SEMA4D (cSEMA4D) saturation by VX15/2503, and (2) the cell membrane expression levels of cSEMA4D. Conclusions: This assay specifically and reproducibly measured cSEMA4D saturation and expression levels. Evaluation of the SEMA4D‐specific PD markers were critical in determining the clinical saturation threshold of cSEMA4D by VX15/2503. © 2015 he Authors Cytometry Part B: Clinical Cytometry Published by Wiley Periodicals, Inc.